LVRT Control Strategy For DC Microgrids Considering the Characteristics of PV/Storage/Load - Yan LI; Zhan WANG; Xun HUANG; Huiyuan ZHANG; Darui HE (Zhongguo dianli)
Low voltage ride-through (LVRT) of grid-connected DC microgrid has been driving academic attentions. Firstly, the structure and operation principle of DC microgrids are developed to obtain the analytical expression of DC bus voltage. Secondly, based on different voltage sags and the maximum current limitation of the converter, a hierarchical coordinated control strategy of bus voltage is proposed considering the characteristics of PV/storage/load. Then according to the fluctuation range of bus voltage and the power state of microgrid, operation modes of DC grid unit are adjusted comprehensively to realize LVRT, which can improve the power balance as well as the stability level of DC bus voltage during LVRT. Finally, a simulation example is built on the platform of MATLAB/Simulink to verify the feasibility of the LVRT strategy and the effectiveness of the control strategy on DC bus voltage.